Analysis of obstacles to adoption of solar energy in emerging economies using spherical fuzzy AHP decision support system: A case of Pakistan - Khurram Shahzad; Daud Abdul; Muhammad Umar; Adnan Safi; Shoaib Maqsood; Abdul Baseer; Baozhou Lu (Energy Reports, 2023)
Adopting suitable energy policies that consider the existence of main obstacles could make the development of solar energy systems much smoother. Several obstacles have been placed in the way of solar energy development in Pakistan, which has prevented its growth from reaching a satisfactory level. In order to tackle these issues, it is necessary first to recognize the obstacles that stand in the way of implementing solar energy. So, this research aims to find and rank the obstacles to the expansion of solar power in Pakistan using a novel spherical fuzzy analytical hierarchy process. The results revealed that the economic obstacles category (21.46%) ranks highest among major categories. In contrast, the overall global ranking of sub-obstacles showed that budget constraints (4.68%), lack of access to credit/capital (4.52%), political instability (4.51%), high investment risk and operation cost (4.42%), and partnership issues (4.37%) are the more critical five sub-obstacles than the rest of the twenty-one obstacles within different categories. In addition, recommendations are made for the elimination of the obstacles. The current study has policy implications for policymakers, researchers, and practitioners involved in the solar sector in the country. Furthermore, it may help develop strategies for the smooth deployment of solar energy in Pakistan.